2017
DOI: 10.1017/s1368980017000556
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and behaviours towards high body weight among adults in Northeast China

Abstract: Body weight misperception was common among adults from Jilin Province.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
0
1
1
Order By: Relevance
“…A recent review concluded that self-management interventions are effective in adults with low health literacy and a chronic physical illness [20]. Low educational attainment and having experienced poverty and/or famine during the 1960s likely explain why older women often do not manage their weight or have misconceptions about maintaining a healthy weight [21]. However, in our study, although both groups gained weight, the intervention group gained less than the control group.…”
Section: Discussioncontrasting
confidence: 55%
“…A recent review concluded that self-management interventions are effective in adults with low health literacy and a chronic physical illness [20]. Low educational attainment and having experienced poverty and/or famine during the 1960s likely explain why older women often do not manage their weight or have misconceptions about maintaining a healthy weight [21]. However, in our study, although both groups gained weight, the intervention group gained less than the control group.…”
Section: Discussioncontrasting
confidence: 55%
“…Vücut ağırlığının doğru bir şekilde algılanması, mevcut kilo durumunun farkındalığını sağlamakla birlikte optimal vücut ağırlığı kontrolü ve kilo ile ilişkili hastalıkların önlenmesi için gereklidir (5,6). Ancak son yıllarda obezitenin bir halk sağlığı sorunu olduğunu gündeme getirmek için gösterilen çabalara rağmen, kendisini fazla kilolu/obez olarak algılayan obez yetişkin oranlarının azaldığı, önemli bir kısmının kilo durumlarını hafife aldıkları ve kendilerini olduklarından daha sağlıklı bir kiloda düşündükleri öne sürülmektedir (4,(7)(8)(9)(10)(11). Yedi yıllık izlem çalışmasında kendilerini kilolu olarak algılayan bireylerin zaman içinde olumlu sağlık algılarının azaldığı, daha fazla fizyolojik sorunlar (kardiyolojik, metabolik ve enflamatuvar vb.)…”
Section: Introductionunclassified